The Role of Surface Recombination on the Performance of Perovskite Solar Cells: Effect of Morphology and Crystalline Phase of TiO2 Contact. Issue 21 (8th October 2018) - Idígoras, Jesús; Contreras‐Bernal, Lidia; Cave, James M.; Courtier, Nicola E.; Barranco, Ángel; Borras, Ana; Sánchez‐Valencia, Juan R.; Anta, Juan A.; Walker, Alison B.
Abstract: Herein, the preparation of 1D TiO2 nanocolumnar films grown by plasma‐enhanced chemical vapor deposition is reported as the electron selective layer (ESL) for perovskite solar devices. The impact of the ESL architecture (1D and 3D morphologies) and the nanocrystalline phase (anatase and amorphous) is analyzed. For anatase structures, similar power conversion efficiencies are achieved using an ESL either the 1D nanocolumns or the classical 3D nanoparticle film. However, lower power conversion efficiencies and different optoelectronic properties are found for perovskite devices based on amorphous 1D films. The use of amorphous TiO2 as electron selective contact produces a bump in the reverse scan of the current–voltage curve as well as an additional electronic signal, detected by impedance spectroscopy measurements. The dependence of this additional signal on the optical excitation wavelength used in the IS experiments suggests that it stems from an interfacial process. Calculations using a drift‐diffusion model which explicitly considers the selective contacts reproduces qualitatively the main features observed experimentally. These results demonstrate that for a solar cell in which the contact is working properly the open‐circuit photovoltage is mainly determined by bulk recombination, whereas the introduction of a "bad contact" shifts the balance to surface recombination. Abstract : Two different charge recombination mechanisms are distinguished in perovskite solar devices based on electron selective layers of different structural and morphological properties. The impact of the interfacial and bulk recombination processes on the photovoltaic performance and hysteresis found in the IV curve measurements is analyzed.